O curso de Licenciatura em Educação Física: as contribuições dos estágios curriculares supervisionados para a formação de professores reflexivos - Kronbauer, Carla Prado (2013)
The following paper conveys the Researching Approach of Formation, knowledge, and Professional Development (PPGE/CE/UFSM) and aimed to analyze how students of Majoring of Physical Education at the CEFD/UFSM featuring reflections about their teaching practice in disciplines Supervised Internship I, II and III, and the relation of these skills to the processes of reflexivity. This research was justified by the importance of understanding how the training courses of physical education teachers in our country are adapting to the current reforms in the structures curriculum from the enactment of the National Curriculum Guidelines for Teacher Training Basic Education and National Curriculum Guidelines for Undergraduate course in Majoring of Physical Education, as well as emphasize the need for reflective teaching to be ingrained throughout the curriculum of teacher education, so that future teachers feel encouraged to reflect critically about their actions as teachers. The methodological approaches that have been adopted followed the assumptions of a qualitative approach case study. The field study was the Center for Physical Education and Sports, Federal University of Santa Maria, with information gathered through the analysis of semi-structured interviews with six scholars who have held each of the disciplines of Supervised Internship I, II and III Degree in Physical Education, and these research participants. To interpret the information collected was used content analysis. It was concluded from this study that the degree in Majoring of Physical Education from CEFD/UFSM is characterized by elements that serve to have a sense of how this course or not influences the quality of future teachers actions that are embedded in it, so that academics to realize its real function as teachers attribute this to its identification as prone educators prior to joining the course, arising from positive experiences when they were students of Basic Education. Regarding the development of the course, which was identified both some disciplines that address knowledge, sometimes far removed from reality school, as the methodologies of some teachers, who still comes from a technical education, no help to a teacher training quality. And as for educational activities, specifically in Curricular Supervised I, II and III, it was deduced that the reflective process is done before, during and after these interventions through teaching so that it is acquired knowledge to base future actions that can teachers. Still, the development of this "thinking about" teaching actions, some aspects (strategies) provided a better analysis of teaching practices so that they can be resignified for the union between theory and practice is characterized as being in a constant search development activities of the teaching-learning process in schools.